(untitled) (Gestão & Regionalidade, 2025)
Ponta Porã and Maracaju are important agribusiness centers and contribute to the socioeconomic development of the State. The research has a documentary approach, and different indicators were evaluated, such as Gross Domestic Product per capita, Municipal Human Development Index, and FIRJAN Municipal Development Index, in addition to the disparity indicator and the Economic Growth Level Index. The objective was to analyze the socioeconomic development indicators considering the economic prominence of these municipalities through the years from 2005 to 2019. The disparity in GDP per capita indicated differences between the cities, with a significant reduction in the disparity from 2012 onwards, with Ponta Porã obtaining an improvement in the indicators. There is a correlation between the GDP of the cities and the growth of the economy of Mato Grosso do Sul, contributing to an increase in employment, wealth generation, and income since several companies that operate in the region are directly or indirectly linked to agribusiness.